35 Uk multi-centre registry of transvenous lead extraction: clinical outcome using different techniques. (5th June 2017) - Martin, Claire; Chooneea, Bashistraj; Gajendragadkar, Parag; Ahsan, Syed; Begley, David; Dhinoja, Mehul; Earley, Mark; Ezzat, Vivienne; Finlay, Malcolm; Grace, Andrew; Heck, Patrick; Hunter, Ross; et al.
Abstract : Introduction: With increasing numbers and complexity of implantable devices, the need for lead extraction is also increasing. There is little UK data available on clinical outcomes. We compiled a multi-centre registry of patients undergoing lead extraction to investigate predictors of success and complications. Methods: Data on all cases at three UK tertiary centres (St. Barts and The Heart Hospital London and Papworth Hospital Cambridge) were collected over 18 months. Cases where leads were >1 year in age or where specialist extraction equipment was used were included (cases=137, leads=268). Results: 69% of patients were male, age 66±16 years (mean±SD). Devices extracted were single chamber PPMs (5%), dual chamber PPMs (42%), CRTPs (6%), single chamber ICDs (6%), dual chamber ICDs (17%) and CRTDs (24%). 76% of ICD leads were dual coil. Number of leads extracted per patient was 2.0±1.0 and time from implantation was 8.3±11.1 years. Leads were extracted using simple traction (39%), traction with locking stylets alone (8%) or dilator sheaths (5%), bidirectional cutting sheaths (38%) or laser (10%). Only 2% of cases required additional femoral access. Specialist equipment was preferentially used for older leads (10.4±13.1 vs 5.2±5.8 years, p<0.001) and for ICD leads (84% vs 53%, p<0.001). The rate of major procedural adverse events (AE) leading to death or emergent surgery was 2.2%, major AEs unrelated to the procedure was 5.8% and minor AEs was 8.7%. Predictors of AEs include patient age (77±28 vs 66±15 years, p=0.05), the age but not type or number of lead (14.8±24.5 vs 7.2±6.0 years, p=0.01), systemic infection a (31 vs 8%, p<0.001), increased creatinine level (142±111 vs 108±23 µmol/L, p=0.011), decreased haemoglobin level (109±23 vs 123±24 g/L, p=0.001) and use of assisted traction or laser over simple traction or mechanical cutting sheaths b (p=0.001) – see Table. Complete extraction was achieved in 95.5% of leads, with only 2.2% with >4 cm of lead remaining in situ . Predictors of procedural failure include age but not type or number of leads (11.1±8.6 vs 8.3±11.3 years, p=0.05), systemic infection c (24 vs 3%, p<0.001) and increased creatinine (162±126 vs 108±66 µmol/L, p=0.012). Laser extraction resulted in 100% success in removing leads. Gender, procedure duration, fluoroscopy time and dose, use of general anaesthesia or temporary pacing was independent of extraction technique and outcome. Discussion: This is the first UK prospective multi-centre study of lead extraction data comparing extraction techniques. Overall there is a low major complication and high success rate with the use of either simple traction or specialist equipment. From our findings, high risk cases can be identified pre-procedure to allow adequate case planning. Laser extraction is clinically effective but is associated with a higher complication rates compared with mechanical cutting sheaths.